NILAI NUTRISI DEDAK PADI YANG DIFERMENTASI DENGAN Rhyzopus oligosporus (Nutrients quality of rice bran fermented with Rhyzopus oligosporus) - Maritje A. Hilakore; Mariana Nenobais; Twenfosel Oc. Dami Dato (JURNAL NUKLEUS PETERNAKAN, 2022)
The experiment was conducted to improve the nutrients quality of rice bran fermented with Rhyzopus oligosporus. The culture used was pure culture and was initiated by rejuvenation of the culture on slanted agar. The method used was experimental using a completely randomized design (CRD) with a 3 x 3 factorial pattern with three factors, namely the first factor was the inoculum level of R. oligosporus 1, 2, and 3% (w/w) and the second factor was incubation time: 24 , 48, and 72 hours to form nine treatment combinations. The combination is L1T1; L1T2; L1T3; L2T1; L2T2; L2T3; L3T1; L3T2 and L3T3. The treatment was repeated three times to form 27 experimental units. Parameters measured were crude protein content, soluble protein, and phytic acid in fermented rice bran. Data were analyzed using analysis of variance (ANOVA) and continued with Duncan's test to compare between treatments. The measurement results concluded that the R. oligosporus inoculum level of 2% and incubation time of 72 hours (L2T3) affected the increase in crude protein content (10.88 to 14.27%), soluble protein (from 6.14 to 9.07%), and decrease phytic acid (5.48 to 2.27%).